Pelatihan Kewirausahaan Kebab Untuk Mebuka Peluang Usaha Baru Bagi Masyarakat Desa Toar di Toar - Novita Indrawati; Azlan Ramadhan; Ade Desma Safitri; Suri Yulan Purba; Citra Intan Sari; Risma Yanti; Nurazizah S; Sherly Indah Permata; Ilham Vikri; Achmad Dadang Hidayah; Andi Aprizal Maulana (Asosiasi Dosen Akuntansi Indonesia, 2022)
Toar Village is one of the villages located in Gunung Toar District, Kuantan Singingi Regency. In Toar Village, there are still a small number of MSMEs, there are still many housewives who have free time. The purpose of implementing this Community Service is as a form of implementing Real Work Lectures (Pengabdian) at the University of Riau to provide Entrepreneurship Training related to Poverty Reduction. In addition, one of the goals of community service is also to be able to provide new ideas, as well as motivate and provide entrepreneurship training for housewives to be able to improve the family economy and the village economy. The target to be achieved is that people become creative and entrepreneurial by being able to create their own ideas about products that will be used for MSMEs. The product that will be an example in entrepreneurship training is Kebab. The method used is the Planning Method, Implementation Method, and Evaluation Method. The results of the implementation of this entrepreneurship training are expected to improve the economy.